The predictive validity of the interRAI ED screener for predicting re-presentation within 28 days for older adults at a regional hospital emergency department. (September 2019) - Taylor, Andrea; Broadbent, Marc; Wallis, Marianne; Marsden, Elizabeth
Abstract: Background: The rapid screening of older adults in the Emergency Department (ED) at risk of adverse events is considered useful. The aim of this study was to evaluate the predictive validity of the interRAI ED screener for re-presentation to the ED within 28 days. Method: A prospective cohort study with convenience sampling of 687 adults aged 70 years or older, and eligible for discharge, was conducted. The interRAI ED screener was utilised by specialist nurses with gerontology expertise. We reviewed electronic medical databases at 28 days for re-presentation data. Area under the receiver operating curve (AUROC) characteristics was computed to determine tool accuracy. Results: The interRAI ED screener demonstrated an AUROC of 0.55 and a P value of 0.09. The overall re-presentation rate within 28 days to the ED was 19.5%; and of re-presentations the majority scored low risk using the interRAI ED screener. Conclusion: When administered by specialised nurses in the ED, the interRAI ED screener demonstrated poor discriminatory ability to predict 28-day re-presentation to the ED of older adults. Whilst the interRAI ED screener was not helpful in identifying those at risk of re-presentation, the results reinforced the need for all older adults to be assessed more comprehensively than through superficial screening.